A successful case of preimplantation genetic testing for monogenic disorder for aplasia cutis congenita - Yang, Xiu-Fang; Shi, Shang-Wen; Ye, Yun; Chen, Kang (Frontiers in Pediatrics, 2022)
Background Aplasia cutis congenita (ACC), also called congenital cutaneous hypoplasia, is a serious disease in newborns. Children with ACC often die due to wound infections and bleeding. How the incidence of ACC can be reduced is a question that needs to be solved urgently. Case report We reported a mother who had delivered two children with ACC, both of whom were diagnosed with ACC type VI, skin defects, limb deformities, and congenital heart malformations. One infant died a few days after birth, and another died in utero in the second trimester. Genetic testing in both children showed a heterozygous mutation in the ITGB4 gene [17q25 exon 8, c.794dupC, (p.Ala266fs) and exon 15, c.1860G>A]. The mother later successfully gave birth to a healthy baby using Preimplantation Genetic Testing for Monogenic disorders(PGD-M). Conclusion The PGD-M technique is highly valuable in reducing the incidence of ACC and improving the prognoses of newborns.